Need Analysis of English Tourism: The Evidence from The Employees of Tourism Industry - Nur Ijabah; Qadrina Lailyn Amrullah (Universitas Muhammadiyah Kalimantan Timur, 2023)
The tourism sector now is seen as a promising sector to increase the nation's foreign exchange revenues. Therefore, a strategic effort such as providing special English language training for tourism employees in order to attract more tourists is needed. However, to produce a research program that can have a major impact on the participants, a needs analysis related to the desired outcomes has to be employed. This study aimed at finding and describing the needs of tourism employees for English language skills. Identification of difficulties during the interaction process in the field is also the focus of research so that it can be used as input in designing training programs. This research is quantitative research with survey research methods. A questionnaire with open and close-ended questions was given to 22 tourism employees at and around Gili Labak Island. The data were analyzed with mathematical computation to obtain the frequency, percentage, and mean scores. The results showed that the most important skills to be mastered by the tourism employee was listening skill (m= 4,5), followed by speaking (m=4,4), writing (m=4,1), and reading (m=3,9) respectively. In terms of problems faced by the tourism employee, they revealed that speaking skill was the most skill that experienced frequent errors during the interaction, then followed by listening, reading, and writing.